Development of Models for Interpreting Mental Health Problems in an International and Armenian Context - Khachatryan, Gohar (Journal of Sociology: Bulletin of Yerevan University, 2023)
This article presents the sequence of models for interpreting mental health problems, the formation of public perceptions of mental health problems influenced by each of the models and setting priorities for state policy. The article presents a summary of both international and Armenian discourses regarding the development of models, based on the analysis of scientific works and domestic legal regulations. International debates revolve around the recent discussion on the contradistinction between the social model and the human rights-based model. The author describes the arguments and critics of all parties of the debate in a detailed manner leaving the reader to make their own conclusions, whereas in the context of Armenia, the author develops the perspective of introducing human rights-based model as a distinct subject of study.